PRODUCTIVITY OF TOMATO (Lycopersicum esculentum L) GROWN UNDER PITCHER IRRIGATION AS AFFECTED BY NUMBER OF PLANTS AND RATES OF POULTRY MANURE PER POT AT SUDANO-SAHELIAN REGION OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
These experiments were conducted at Federal University Dutsin-Ma Teaching and Research Farm, Badole (Longitude 07029'29" E and Latitude 12027'18" N) during the dry seasons (November to March) of 2015 and 2016. The experiments were conducted to determine the optimum number of tomato plants and quantity of poultry manure per pot in a pitcher irrigation system. The treatments consisted of 2, 4, and 6 tomato plants per pot and 0, 1 and 2 kg of poultry manure per pot. The nine treatments were factorized and laid out in a randomized complete block design (RCBD) and replicated three times. The highest tomato fruit yield per pot was obtained from the treatment with four plants and 2kg of poultry manure per pot, while larger fruits were obtained in treatments with 2 plants and 2kg of poultry manure per pot. The number, size and weight of tomato fruits were significantly (P
Keywords: Clay pot, Pitcher irrigation, Poultry manure, Tomato fruit